Conceptualising service quality and technology factor as drivers for continuous usage of broadband among rural dwellers in Malaysia - Muraina, Ishola Dada; Sheik Osman, Wan Rozaini; Ahmad, Azizah (2012)
Information and communication technology(ICT) have found to be a key player in making IT and IT-enabled services of some countries a tradable and leading to the fastest average annual growth in their economy.Broadband which is the arm of ICT is believed to be a vital links of enhancing competitiveness in an economy and sustaining economic growth. Despite the significances of broadband, broadband connectivity is not yet seen to have enormous potential to increase national competition in Malaysia, especially in the rural areas.This shows that there is need to take a drastic step to maintain continuous use of broadband among rural dwellers in Malaysia.This paper presents a model that will aid continuous use of broadband among rural consumers in Malaysia.